2018
DOI: 10.4238/gmr16039914
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Selection of progenies of snap beans using mixed models (REML/BLUP)

Abstract: The purpose of this research was to select the development of superior genotypes of snap beans adapted to edaphoclimatic conditions of the North and Northwest of Rio de Janeiro State, Brazil, applying the mixed model methodology. The test was installed and carried out in the experimental area of the Instituto Federal Fluminense (IFF), located in the municipality of Bom Jesus do Itabapoana, Rio de Janeiro State, Brazil, using the modified SSD (Single Seed Descent) method. The experiment was of randomized block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Thus, the REML/Blup methodology is an important statistical tool, which can help breeders to conduct breeding programs during selection processes. Similar results demonstrating the potential for the REML/Blup technique were seen in studies on beans, by Sousa et al (2017), Gomes et al (2018), and Cruz et al (2018); and maize, by Arnhold et al (2009), Oliveira et al (2016), Entringer et al (2016), and Mendonça et al (2016), all confirming the results of this study. ) and mean grain mass, municipality of Jataí, Goiás State, Brazil, UFG, 2018.…”
Section: Predicted Genetic Values (μ + G)supporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the REML/Blup methodology is an important statistical tool, which can help breeders to conduct breeding programs during selection processes. Similar results demonstrating the potential for the REML/Blup technique were seen in studies on beans, by Sousa et al (2017), Gomes et al (2018), and Cruz et al (2018); and maize, by Arnhold et al (2009), Oliveira et al (2016), Entringer et al (2016), and Mendonça et al (2016), all confirming the results of this study. ) and mean grain mass, municipality of Jataí, Goiás State, Brazil, UFG, 2018.…”
Section: Predicted Genetic Values (μ + G)supporting
confidence: 91%
“…Furthermore, they facilitate the study of new methodologies that enhance their efficiency and lead to future research. As such, the estimate of genetic progress is a significant option for assessing breeding programs (Cruz et al, 2018). Hence, the goal of the current study is to select top cross hybrids of green maize for yield from partially inbred S 1 lines, based on genetic values by means of the REML/Blup method, and to estimate important genetic parameters for green maize breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the selection of superior genotypes is possible, although more costly. Cruz et al (2018) and Souza et al (2018) observed similar results, estimating values of low magnitude and lower than the experimental coefficient of variation for green bean and black bean genotypes, respectively.…”
Section: Resultssupporting
confidence: 55%
“…In the disconnected factorial design, the formation of small groups of crossings, usually 3 × 3 or 4 × 4, is recommended, thus maximizing the number of parents to be evaluated in a single experiment (Burdon & Buijtenen, 1990). Unbalanced data are common in these cases, so to obtain reliable estimates of variance components and genetic and genotypic values, the restricted maximum likelihood (REML) and best linear unbiased prediction (BLUP) methodologies are considered the best statistical tools (Cruz et al, 2018;Piepho, Möhring, Melchinger, & Büchse, 2008;Resende, 2002;Resende, 2015). Piepho et al (2008) suggested the application of BLUP in plant breeding along with the inclusion of pedigree information to explore genetic correlations between relatives and obtain the most accurate estimates.…”
Section: Introductionmentioning
confidence: 99%